2015
DOI: 10.1016/j.juro.2015.02.2945
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Complications following Artificial Urinary Sphincter Placement

Abstract: The most common complication of artificial urinary sphincter placement is urinary retention. Serious adverse events following artificial urinary sphincter placement are rare. Postoperative urinary retention is associated with adverse short-term device survival rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 15 publications
1
23
1
3
Order By: Relevance
“…Their pooled analysis demonstrated 8.5 % infection and erosion rate, 6.2 % mechanical failure, 7.9 % urethral atrophy, and 26 % reoperation rate. More recently in a retrospective analysis examining 179 primary AUS implantations over a 2-year period, Linder et al [11] showed an overall complication rate of 35 % in the immediate 6 weeks following surgery. Complications include urinary retention (31 %), device infection (2 %), urethral erosion (2 %), and cellulitis (1 %).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their pooled analysis demonstrated 8.5 % infection and erosion rate, 6.2 % mechanical failure, 7.9 % urethral atrophy, and 26 % reoperation rate. More recently in a retrospective analysis examining 179 primary AUS implantations over a 2-year period, Linder et al [11] showed an overall complication rate of 35 % in the immediate 6 weeks following surgery. Complications include urinary retention (31 %), device infection (2 %), urethral erosion (2 %), and cellulitis (1 %).…”
Section: Discussionmentioning
confidence: 99%
“…It can serve as a quality metric that may allow surgeons to identify areas of potential improvement in their practice. Data regarding male slings and AUS implantation complications have typically come from retrospectively reviewed large single-institution cases series [10,11] and identified from administrative billing data that have inherent limitations [12].…”
mentioning
confidence: 99%
“…After the analysis of the full texts, 14 studies were included in our evaluation. [25][26][27][28][29][30][31][32][33][34][35][36][37][38] The main reasons for exclusion were: studies aiming only to describe the surgical technique, a series of cases with a small number of patients included (n < 10), and a narrative review.…”
Section: Resultsmentioning
confidence: 99%
“…[35][36][37][38] (C) A before--and-after study applied a longer period of primary deactivation (12 weeks) in irradiated patients. There is no evidence to support a primary deactivation period greater than six weeks.…”
Section: Resultsmentioning
confidence: 99%
“…Jeigu šlapimo susilaikymas trunka ilgiau nei savaitę, tikėtina priežastis -netinkamas manžetės dydis. Tada reikalinga pakartotinė operacija manžetei pakeisti [49].…”
Section: Komplikacijosunclassified